2016
DOI: 10.2169/internalmedicine.55.6815
|View full text |Cite
|
Sign up to set email alerts
|

Restless Bladder in an Elderly Woman: An Unusual Feature or a Variant of Restless Legs Syndrome?

Abstract: We herein report an elderly patient with a history of restless legs syndrome (RLS) who developed unpleasant sensations in the lower abdomen and perineum. The patient's symptoms occurred during the evening and at rest and forced the patient to void, resulting in some symptom relief. Urological examinations and spinal magnetic resonance imaging findings were unremarkable. The adjunctive use of rotigotine resolved her symptoms. The symptoms were considered to be restless bladder . Further studies are required to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Reports of RLS variant has been increased and expand the clinical spectrum. Various other parts of the body than legs can be involved from arms, abdomens, face, head, oral cavity, bladder and genital area [9,11,[20][21][22]. Supportively, this case did not report daytime sleepiness, which was also supporting feature of RLS [6].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Reports of RLS variant has been increased and expand the clinical spectrum. Various other parts of the body than legs can be involved from arms, abdomens, face, head, oral cavity, bladder and genital area [9,11,[20][21][22]. Supportively, this case did not report daytime sleepiness, which was also supporting feature of RLS [6].…”
Section: Discussionsupporting
confidence: 56%
“…The prevalence are reported in a few% of adults in Japanese population, similar to European and American population [6][7][8]. RLS cases have also a various symptom form mainly legs symptom to head, oral cavity, abdomen, perineum, which are recognized as RLS variant cases [9][10][11]. The pathology of RLS is suggested to be from dopaminergic dysfunction on the level of dopamine receptors, and iron deficiency, kidney dysfunction, diabetes mellitus are the exacerbation factor [6].…”
Section: Introductionmentioning
confidence: 79%
“…A few authors have reported restless bladder mimicking overactive bladder syndrome. Restlessness in atypical body parts usually coincides with the classical RLS of lower limbs 11. Besides these, a significant association between RLS and pain of different origins have been reported in the literature 13.…”
Section: Discussionmentioning
confidence: 92%
“…IRLSSG consensus diagnostic criteria for RLS mention that arms (restless arms syndrome) and other body parts may be involved in addition to the legs. The abnormal unpleasant sensation may be noted in the abdomen (restless abdomen), genital area (restless genital syndrome), oral cavity (restless mouth syndrome), face, chest and back, and neck and head 7–12. The unpleasant sensation in different parts of the body may mimic several other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As awareness of RLS has grown, several reports revealed that sensory disorders similar to RLS initially con ned to the arms, abdomen, and perineum occasionally occur [4][5][6][7][8][9][10]. These reported cases also partially meet the diagnostic criteria of RLS.…”
Section: Introductionmentioning
confidence: 98%